Comparison of Fundamental Analysis of PT Sharia Shares. Indofood Sukses Makmur Tbk (INDF) & PT. Mayora Indah Tbk (MYOR) in 2022 as an investment decision - Nurkhosiah, Siti; Suhendar, Fikry Ramadhan (Ta'amul: Journal of Islamic Economics, 2024)
Investment is an alternative for an investor, a company to develop its business, while for a company getting additional new capital from investors which the company uses is basically aimed at developing the company's operations. However, investors must carefully choose a company as a place to gain profits, so this research aims to determine the level of financial health of a company in operational activities as one of the foundations for an investor to make investment decisions. An investor needs to carry out risk management in investing to minimize losses that will impact the company's performance. There are various kinds of investments that can be made by companies or individuals, starting from Sukuk, SBSN, SUN, and so on. This research uses empirical qualitative methods with company fundamental analysis, namely by using secondary data from the financial reports of PT. Indofood Sukses Makmur Tbk (INDF) & PT. Mayora Indah Tbk (MYOR) in 2022 by analyzing financial reports with fundamental analysis of shares. the Sharia. This fundamental analysis uses ROE, ROA, PER, DER, PBV, NPM, GPM and ROI calculations to measure how a company has optimal operational performance for long-term investment activities. The results of this research inform that the performance of the Company PT. Mayora Indah Tbk is better than the performance of PT. Indofood Sukses Makmur Tbk in 2022 when viewed from the financial report with fundamental analysis. Both companies can be categorized as good if seen from their financial reports, only that PT. Mayora Indah Tbk is superior to PT. Indofood Sukses Makmur Tbk so that it can provide information for investors in developing their business.